Electrocatalytic Oxygen Reduction on Metalloporphyrins. Second Coordination Sphere Substituents on the Ligand: Electronic and Steric Effects Through Pocket and Extended Structures and Their Effect on the Electrocatalytic Activity - Zagal-Moya, J; Zagal-Moya, J; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Silva-Molina, C; Silva-Molina, C; Agurto-Doren, N; Agurto-Doren, N; Martinez-Gomez, F; Olguín-Choupay, C; Olguín-Choupay, C; Jara-Reyes, G; et al. (Academic Press, 2024)
The rational design of new electrocatalysts remains a continuous challenge in pursuing high-performance fuel cells free of precious metals. In this work, we report MN4-type metal-complex catalyst based on bio-inspired systems, i.e., metalloporphyrins complexes that include the second coordination sphere as the central axis for a relevant improvement in catalysis. Two isostructural systems, tetra-ferrocenyl-triazole metalloporphyrin (pocket vs. extended structures), were synthesized to study the role of the second coordination sphere on the electrochemical oxygen reduction reaction (ORR). The electrocatalysis results show that both porphyrin systems promote the ORR via four electrons. The system that presents a pocket structure (o-Fc4TPP-FeIII) exhibits a foot of the wave 72 mV more positive than its analog with an extended structure (p-Fc4TPP-FeIII). Rotating ring-disc experiments evidenced that the presence of H-bonding and distal redox groups would be directly related to faradaic efficiency for the 4-electron reduction to water, with an 86 % for the pocket structure and 76 % for the extended system. This study allows us to confirm the molecular scaffolding function by comparing two systems that present the same functional groups but in different chemical environments, providing valuable information regarding the steric-spatial parameters that play a role in the ORR. © 2024 Elsevier Inc.